2018
DOI: 10.4314/jfas.v9i6s.64
|View full text |Cite
|
Sign up to set email alerts
|

Churn classification model for local telecommunication company based on rough set theory

Abstract: Customer care plays an important role in a company especially in Telecommunication Company. Churn is perceived as the behaviour of a customer to leave or to terminate a service. This behaviour causes the loss of profit to companies because acquiring new customer requires higher investment compared to necessary to consider an efficient classification model to reduce the rate of churn. Hence, the purpose of this paper is to propose a new classification model based on the Rough Set Theory to classify customer chu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Since, the last several years, aspect extraction is becoming a widely studied area. Multiple approaches were used including supervised as well as unsupervised [7]. Several studies showed that the double propagation approach based on syntactic dependency [8] performs well as compared to many supervised learning techniques [9].…”
Section: Figure 1: Classification Of Sentiment Analysismentioning
confidence: 99%
“…Since, the last several years, aspect extraction is becoming a widely studied area. Multiple approaches were used including supervised as well as unsupervised [7]. Several studies showed that the double propagation approach based on syntactic dependency [8] performs well as compared to many supervised learning techniques [9].…”
Section: Figure 1: Classification Of Sentiment Analysismentioning
confidence: 99%
“…Makhtar et al [16] proposed a model for churn prediction using rough set theory in telecom. As mentioned in this paper Rough Set classification algorithm outperformed the other algorithms like Linear Regression, Decision Tree, and Voted Perception Neural Network.…”
Section: Related Workmentioning
confidence: 99%
“…Random Forest (RF) method is applied and estimated with the help of AUC. Makhtar et al [14] projected an approach for churn prediction under the employment of rough set theory in telecom services. The Rough Set classification approach has surpassed the previous models like Linear Regression, DT, and Voted Perception NN.…”
Section: Related Workmentioning
confidence: 99%